(untitled) (Hekima Review, 2010)
In his book, Kariuki points out the place of women in the society and the need for liberating them from the slavery of patriarchal cultural structures. Like men, women are entitled to benefit from the societal and cultural norms since both men and women are equal. Unfortunately this is not the case in many African societies where women suffer under the authority of men; some suffer oppression caused by the social structures defined by men.